Circulating microRNAs as biomarkers for severe coronary artery disease. Issue 17 (April 2020) - Zhang, Xuelin; Cai, Haipeng; Zhu, Minqi; Qian, Yinfen; Lin, Shanan; Li, Xiaoqiang
Abstract : Abstract: Coronary artery disease (CAD) is the second leading cause of death after stroke in China. Percutaneous coronary intervention (PCI) significantly improves the prognosis of CAD patients. This study aimed to evaluate the diagnostic value of circulating microRNAs (miRNAs) in patients with severe CAD requiring PCI. The plasma miRNA profiles were determined using miRNA microarray. The relative expression levels of differentially expressed miRNA were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Nine miRNAs (ebv-miR-BART12, ebv-miR-BART16, let-7i-5p, miR-130a-3p, miR-26a-5p, miR-3149, miR-3152–3p, miR-32-3p, and miR-149-3p) were differentially expressed between severe CAD and control groups. Four miRNAs (let-7i-5p, miR-32-3p, miR-3149, and miR-26a-5p) validated by qRT-PCR showed good diagnostic accuracy, with the area under the receiver operating characteristic curves (AUCs) of 0.634 (95% confidence interval [CI] 0.528–0.739), 0.745 (95%CI 0.649–0.84), 0.795 (95%CI 0.709–0.88), and 0.818 (95%CI 0.739–0.897), respectively. Furthermore, the combination of these 4 miRNAs exhibited better diagnostic performance compared with any individual miRNA, with an AUC of 0.837 (95%CI 0.763–0.911). These data indicate that plasma let-7i-5p, miR-32–3p, miR-3149, and miR-26a-5p have promising diagnostic value for severe CAD.